Refleksi Diri Sebagai Ide Dalam Penciptaan Seni Lukis - Fikri Hidayatullah; Lalu Aswandi Mahroni G; Sri Sukarni (Jurnal Ilmiah Telaah, 2023)
The purpose of this final project is to visualize several forms of self-reflection in telling personal experiences that become lessons. Self-reflection is the thing that is most attached to the writer's life when approaching the end of the lecture period. The idea of art is to visualize human figures as the subject of paintings that depict different body shapes. The method of realizing ideas is through the preparatory stage or the observation stage of the problems of concept realization or the creation of works of exhibition or display of works. The author presents 15 (fifteen) works of art through figures, all of which are different body shapes. The entire work was made using acrylic paint on canvas of the same size and was made in the year 2022.